2020
DOI: 10.3390/cells9061454
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Overexpression Attenuates Sepsis-Induced Muscle Wasting

Abstract: Sepsis elicits skeletal muscle weakness and fiber atrophy. The accumulation of injured mitochondria and depressed mitochondrial functions are considered as important triggers of sepsis-induced muscle atrophy. It is unclear whether mitochondrial dysfunctions in septic muscles are due to the inadequate activation of quality control processes. We hypothesized that overexpressing Parkin, a protein responsible for the recycling of dysfunctional mitochondria by the autophagy pathway (mitophagy), would confer protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Hence, bioenergetics failure was implicated to contribute to the severity of sepsis-induced muscle wasting [ 162 ]. Indeed, numerous reports have demonstrated the extensive mitochondrial dysfunction that occurs with sepsis-induced muscle wasting [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Mitochondrial dysfunction has been postulated to contribute to sepsis-induced muscle wasting in three ways: (1) diminished energy producing capacity; (2) increased oxidative stress; and (3) deficient satellite cell function.…”
Section: Evidence Linking Mitochondrial Dysfunction With Sepsis-induced Muscle Wastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, bioenergetics failure was implicated to contribute to the severity of sepsis-induced muscle wasting [ 162 ]. Indeed, numerous reports have demonstrated the extensive mitochondrial dysfunction that occurs with sepsis-induced muscle wasting [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Mitochondrial dysfunction has been postulated to contribute to sepsis-induced muscle wasting in three ways: (1) diminished energy producing capacity; (2) increased oxidative stress; and (3) deficient satellite cell function.…”
Section: Evidence Linking Mitochondrial Dysfunction With Sepsis-induced Muscle Wastingmentioning
confidence: 99%
“…In regard to the direct evidence implicating mitochondrial dysfunction as a critical mediator of sepsis-induced muscle wasting, a recent report reveals that overexpression of parkin, a protein responsible for mitophagy (i.e., mitochondrial autophagy), protects muscle against sepsis-induced wasting [ 168 ]. Mitochondria are observed to present a swollen appearance and disorganized morphology in muscle during sepsis [ 165 , 168 , 170 , 176 , 183 ]. However, parkin overexpression during sepsis attenuated altered mitochondrial morphology and prevented myofiber atrophy [ 168 ].…”
Section: Evidence Linking Mitochondrial Dysfunction With Sepsis-induced Muscle Wastingmentioning
confidence: 99%
“…In addition, these loss-of-function studies also highlighted that PARKIN-mediated mitochondrial clearance contributes to proteasome activation during denervation in atrophied slow-twitch muscles [ 253 ]. On the flip side, gain-of-function studies showed that PARKIN overexpression in mice: (i) attenuates the ageing-related and the sepsis-induced muscle wasting and causes hypertrophy in adult skeletal muscle, (ii) increases mitochondrial content and enzymatic activities and (iii) protects from ageing-related increases of oxidative stress markers, fibrosis and apoptosis [ 185 , 186 ]. It is very likely that this role of PARKIN in controlling muscle mass has been evolutionary conserved.…”
Section: E3 Ligases Involved In the Regulation Of Muscle Atrophymentioning
confidence: 99%
“…However, the abundance of a protein does not reflect its enzymatic activity. Furthermore, in models of aging ( Leduc-Gaudet et al, 2019 ) and sepsis ( Leduc-Gaudet et al, 2020 ), skeletal muscle Parkin overexpression has been shown to attenuate morphological and functional mitochondrial defects, possibly through enhanced mitophagy. These studies suggest that Parkin activation is sufficient to induce mitophagy in skeletal muscle.…”
Section: Pink1-parkin-mediated Mitophagymentioning
confidence: 99%